2017
DOI: 10.1159/000475932
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative C-Reactive Protein Values as a Potential Component in Outcome Prediction Models of Metastasized Renal Cell Carcinoma Patients Receiving Cytoreductive Nephrectomy

Abstract: Purpose: To validate preoperative C-reactive protein (CRP) levels as a prognostic marker for survival in a metastasized renal cell carcinoma (mRCC) patient cohort receiving cytoreductive nephrectomy (CN). Patients and Methods: By chart review, 146 mRCC patients receiving CN at our tertiary referral centre from 1997 to 2015 were identified retrospectively. All relevant clinicopathological features including laboratory parameters were collected and correlated to overall survival, progression-free survival and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…A summary of recent studies investigating the prognostic role of CRP level in RCC is shown in Table . Four studies evaluated the pre‐ and post‐treatment CRP value, and the remainder only evaluated the pretreatment value.…”
Section: Serum Protein Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of recent studies investigating the prognostic role of CRP level in RCC is shown in Table . Four studies evaluated the pre‐ and post‐treatment CRP value, and the remainder only evaluated the pretreatment value.…”
Section: Serum Protein Markersmentioning
confidence: 99%
“…A summary of recent studies investigating the prognostic role of CRP level in RCC is shown in Table 1. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Four studies evaluated the pre-and post-treatment CRP value, and the remainder only evaluated the pretreatment value. The cut-off value for high versus low CRP level varied from 0.3 to 10 mg/dL, with most studies using a cut-off value of approximately 0.5 mg/dL.…”
Section: Crp In Rccmentioning
confidence: 99%
“…Several previous studies have found that the level of CRP negatively correlates with both OS and cancer-specific survival (25)(26)(27)(28). Reichle et al suspected that tumor cells produce CRP, which is thought to be the reason why patients with larger tumor volumes have higher CRP levels (29).…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] Kalogirou et al demonstrated the effectiveness of determining preoperative CRP level as a prognostic marker of survival in a cohort of patients with mRCC undergoing cell-reducing nephrectomy (CN). [ 21 ]…”
Section: Discussionmentioning
confidence: 99%